VERS UN NOUVEL HORIZON EN TRADUCTION AUTOMATIQUE - Al Zboun, Bassel (European Scientific Journal, ESJ, 2014)
This research aims at presenting theoretically a new approach for machine translation systems. It attempts first of all to show the high demands for new techniques of such systems in a world where the telecommunication dominates. Concrete examples are translated and analyzed with the aim of demonstrating some problems of the current software. In view of the results, the researcher suggests integrating the syntactical categories as well as the structures as a whole within the model to improve the results of translation. The research also shows the process through which the translation of the intended text takes place.